Adverse Events Following COVID-19 Vaccination among the Beneficiaries of Sikkim Manipal University: A Cross Sectional Study - Bhutia, Jayden Lhamu; Upreti, Binu; Bhutia, Eden Jamyang; Kar, Sumit; Zaman, Forhad Akhtar (Indian Journal of Community Health, 2021)
Background: Covid-19, an infection caused by SARS- CoV2 has claimed millions of lives since late 2019 with no curative measures. In India, 4 vaccines have been approved for use i.e. Serum Institute’s Covishield, Bharat Biotech’s Covaxin, GRIEM’s Sputnik V and Moderna’s Covid-19 vaccine. Aims: This study aims to find the adverse events following Covishield vaccination among the beneficiaries of Sikkim Manipal University, Sikkim. Material &Methods: A cross sectional study was conducted among the beneficiaries of Sikkim Manipal University to find out the adverse events following the first dose of vaccination. The data was collected using a self-administered questionnaire when the beneficiaries came for their second dose of vaccination. Microsoft Excel and SPSS version 27 was used for statistical analysis. Results: Out of 716 study participants majority i.e. 79.5% of the study participants developed adverse events following their first dose with maximum (73.8%) complaining of pain at the site of infection followed by fever (65.2%). Conclusions: Vaccines may prevent diseases, but it also brings about adverse effects, be it minor or major. Hence, many studies are required to study their full-fledged side effects and the means to overcome them.